2022
DOI: 10.3390/f13121971
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Genetic Variability in Contrasting Latitudinal Fagus sylvatica L. Provenances

Abstract: The adaptive capacity of a species and its population is determined by both genetic and epigenetic variation, which defines the potential for adaptive evolution and plastic response to environmental changes. In this study, we used Methylation Sensitive Amplified Polymorphism (MSAP) and Amplified Fragment Length Polymorphism (AFLP), similar genome-wide profiling techniques, to analyze the epigenetic and genetic variability in European beech provenances from Germany (DE), Spain (ES) and Sweden (SE), representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
1
4
1
Order By: Relevance
“…Concerning the correlations between genetic and epigenetic distances, we found a nonsignificant negative correlation, contrary to [28], where Fagus sylvatica populations were studied, and to [32], who studied Viola elatior natural populations, as both found significant positive correlations. Furthermore, mean percentage of polymorphic genetic and epigenetic variation was found to be 50.11% and 36.75%, respectively, indicating comparable lower results with previous studies for Prunus avium [10], Pinus nigra [16], Fagus sylvatica [28], and Quercus ilex [31]. AMOVA results partitioned 94% and 99% of epigenetic and epigenetic variation, respectively, within subpopulations, and results were in agreement with previous published studies for F. sylvatica [28], P. avium [10], P. nigra [30], etc.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Concerning the correlations between genetic and epigenetic distances, we found a nonsignificant negative correlation, contrary to [28], where Fagus sylvatica populations were studied, and to [32], who studied Viola elatior natural populations, as both found significant positive correlations. Furthermore, mean percentage of polymorphic genetic and epigenetic variation was found to be 50.11% and 36.75%, respectively, indicating comparable lower results with previous studies for Prunus avium [10], Pinus nigra [16], Fagus sylvatica [28], and Quercus ilex [31]. AMOVA results partitioned 94% and 99% of epigenetic and epigenetic variation, respectively, within subpopulations, and results were in agreement with previous published studies for F. sylvatica [28], P. avium [10], P. nigra [30], etc.…”
Section: Discussioncontrasting
confidence: 89%
“…Genetic diversity has been traditionally considered as the primary source for biodiversity, evolution, and adaptive capacity. However, in recent years, numerous studies have shown the significant role that epigenetic plays in adaptation ( [7,13,[24][25][26][27][28] and in phenotypic plasticity [7,29]. Variation in DNA methylation may or may not depend on underlying genetic variation in DNA sequences, which further complicates efforts to resolve the role of DNA methylation [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth traits of trees are shaped by both environmental and genetic factors [46,47]. This study focused on 11 provenances of F. hodginsii, including the local provenances within Fujian Province and the non-local provenances from other provinces.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in 1,380,310 SNPs across all sampled individuals used in further analyses. To date, patterns of F. sylvatica genetic diversity and structure have been studied with marker-based approaches including allozymes (Gallois et al 1998), AFLP (Pluess and Weber 2012, Guevara et al 2022), microsatellites and, more recently, SNPs in candidate genes (Csilléry et al 2014, Pfenninger et al 2020, Meger et al 2021, Cuervo-Alarcon et al 2021) and whole-genome sequences from limited area of the specie range (Stefanini et al 2023). We are not aware of another study so far that used whole-genome sequences from across the range of F. sylvatica .…”
Section: Methodsmentioning
confidence: 99%